Implementasi Kebijakan Rencana Tata Ruang Wilayah: Studi Intensifikasi Ruang Terbuka Hijau Di Taman Layak Anak Kota Cilegon - Alfina Sulistiani; Dini Gandini Purbaningrum (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Regulation No. 1 of 2020, focusing on the creation of "Green Open Spaces" within Cilegon City to enhance ecological quality. The study particularly examines the Child-Friendly Park in the city and identifies shortcomings in infrastructure and programs supporting children's growth and development. The research aims to analyze the policy implementation through a descriptive qualitative approach, utilizing Van Meter and Van Horn's theory (1975) with six indicators: objectives, resources, agent characteristics, disposition, interorganizational communication, and the economic, social, and political environment. The findings reveal several deficiencies in policy implementation: inadequate achievement of policy objectives, suboptimal utilization of resources (including personnel, budget, and technology), insufficient involvement of implementing agents (specifically, Disperkim's lack of appropriate programs and standard operating procedures), satisfactory stakeholder communication, positive attitudes among implementers, and a mixed economic, social, and political environment that lacks significant support for the policy's realization in Cilegon City's Children's Park.